Analysis and manegement of laminar blood flow inside a cerebral blood vessel using a finite volume software program for biomedical engineering. (July 2020) - Yan, Shu-Rong; Sedeh, ShahabNaghdi; Toghraie, Davood; Afrand, Masoud; Foong, Loke Kok
Highlights: Non-Newtonian blood flow in the cerebral blood vessels studied. We used Magnetic Resonance Image to take Digital Imaging. Impact of Reynolds number, power-law indexes and heat fluxes are investigated. Pressure drop increase with increasing the Reynolds number and power-law index. The maximum Nusselt number vessels accrued in the running position of the body. Abstract: Background and objective: Hemodynamic blood flow analysis in the cerebrovascular is has become one of the important research topics in the bio-mechanic in recent decades. The primary duty of the cerebral blood vessel is supplying Glucose and oxygen for the brain. Methods: In this investigation, the non-Newtonian blood flow in the cerebral blood vessels studied. For modeling the geometry of this problem, we used Magnetic Resonance Image (MRI) approach to take Digital Imaging and Communications in Medicine (DICOM) images and using an open-source software package to construct the geometry, which is a complicated one. The power-law indexes, heat flux, and Reynolds number range in the investigation are 0.6 ≤ n ≤ 0.8, 5 ≤ q ≤ 15 Wm −2 and 160 ≤ Re ≤ 310 . Effects of Reynolds number, power-law indexes and heat fluxes are investigated. Results: We found that the pressure drop increase with increasing the Reynolds number and power-law index. The maximum Nusselt number in the cerebral blood vessels accrued in the running position of the body in n = 0.8. Also, the highest average wall shear stress occurs in maximum power-law indexes and Reynolds number. Conclusion: By increasing the power-law index and Reynolds number, the wall shear stress increases.